Building Energy Performance Assessment Using an Easily Deployable Sensor Kit: Process, Risks, and Lessons Learned - Frei, Mario; Deb, Chirag; Nagy, Zoltan; Hischier, Illias; Schlueter, Arno (Frontiers in Built Environment, 2021)
In the building and construction sector, the mismatch between predicted and measured energy consumption is a well-known phenomenon called the performance gap. A promising approach to reduce the performance gap and thus improve the current building energy performance assessments are methods based on in-situ measurements. In this work, we present a building assessment process based on a novel, easily deployable wireless sensor kit. The basic sensor kit for building energy assessment presented in this study consists of a heating energy input node, several indoor temperature nodes, an outdoor temperature node, and a heat flux sensor. Specifically, the study outlines a medium-scale deployment of the sensor kit in eight occupied single-family homes in Switzerland and identifies the benefits of such an approach in the estimation of the overall heat loss coefficient and U-values. The findings of this study suggest that such sensor kits could be effectively used for rapid building performance assessment, and the paper concludes by outlining the potential benefits and implementation challenges of a larger scale study.